MARKETING STRATEGIES IN THE GLOBAL DIGITAL ENVIRONMENT OF ECONOMIC FACTORS: IMPACT ON CONSUMER BEHAVIOR OF BUILDING MATERIALS - Marchenko, Svitlana (SWorld-Ger Conference proceedings, 2024)
The impact of economic factors and the latest marketing technologies, such as artificial intelligence, augmented reality, big data analytics and interactive advertising, etc., on consumer behaviour was analysed. It examines how these tools allow companies